2020
DOI: 10.1108/srj-01-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Relationships and impacts of perceived CSR, service quality, customer satisfaction and consumer rights awareness

Abstract: Purpose The purpose of this paper is threefold: first, to examine the effects of perceived corporate social responsibility (CSR) on service quality, satisfaction and repurchase intention; second, to investigate the mediating (unique and serial) effects of service quality and satisfaction; and third, to determine the moderating effects of consumer rights awareness (CRA) on the relationship between perceived CSR and consumer responses. Design/methodology/approach Survey data was collected from a sample of 604 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 61 publications
2
29
1
3
Order By: Relevance
“…Furthermore, findings from a study in Nigeria by K. B. Bello et al (2020) confirmed that consumers with higher knowledge of rights have a higher tendency to favourably appraise the product/ services and to repeat purchase from a company perceived to be compliant, mostly in corporate social responsibility issues. Therefore, it is logical to assume that:…”
Section: Research Hypothesesmentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, findings from a study in Nigeria by K. B. Bello et al (2020) confirmed that consumers with higher knowledge of rights have a higher tendency to favourably appraise the product/ services and to repeat purchase from a company perceived to be compliant, mostly in corporate social responsibility issues. Therefore, it is logical to assume that:…”
Section: Research Hypothesesmentioning
confidence: 94%
“…A similar study in Nigeria showed that consumers with high knowledge of rights tend to prefer products or services and to repeatedly buy from a company perceived to be compliant, mostly in corporate social responsibility issues (K. B. Bello et al, 2020).…”
Section: Implications For Theorymentioning
confidence: 98%
See 2 more Smart Citations
“…How salespeople handle the purchase? And the role price discounting plays in it are two important factors for price delegation (Bello et al, 2020). In price delegation, a salesperson can offer a discount to a customer based on his previous knowledge of the market (Curina et al, 2020).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%